Speech Acts in Pragmatic Linguistics: A Conceptual Review and Its Applications - Kabalmay, Taqiyuddin; Susanto, Djoko (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study aims to examine in depth how speech act theory is applied in various communication contexts and to explore linguists' perspectives regarding this theory. A qualitative method was employed through a literature review approach, which included several stages: data collection, analysis, and validation. The data were gathered from relevant literature, both printed and digital, about the concepts of speech acts and pragmatics. This study investigates the role of speech acts in shaping the understanding of social interaction dynamics and the cultural values embedded within them. The findings indicate that speech acts function as instruments for performing communicative actions. In this context, a speaker's utterance carries a specific intention or meaning, recognizing that people do not speak without purpose. Various descriptive terms are used to illustrate the communicative intent behind utterances. Understanding speech acts is relevant to linguistic analysis and has practical applications in enhancing communication effectiveness across diverse social and cultural settings.